The circuit of culture: A model for journalism history - Schmidt, Thomas R. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
More than forty years ago, James W. Carey published his seminal essay “The Problem of Journalism History” and called for a “cultural history of journalism.” While his plea has posed intriguing questions, it has fallen short on providing specific answers to the challenges of contemporary journalism history. I propose that the circuit of culture model offers promising research strategies to flesh out Carey’s idea of journalism as a cultural practice. The circuit of culture model re-articulates Carey’s call in numerous ways. It circumvents the intangible concept of consciousness and instead focuses on the production, transformation and renegotiation of meaning in a social world structured (albeit not entirely) by regulative and institutional pressures. It puts more emphasis on acknowledging power and asymmetries in society. It accounts for economic pressures without privileging them. While holding on to the holistic notion of culture, the circuit of culture model identifies specific sites for research and thus allows for a more detailed view of the practice and reception of journalism. Ultimately, the circuit of culture approach complements Carey’s vision but re-articulates it in a more specific and nuanced way.
Keywords: JOURNALISM STUDIES; CULTURAL STUDIES; journalism; HISTORY; James W. Carey